Establishing banking market definitions through estimation of residual deposit supply equations - Amel, Dean F; Hannan, Timothy H (Journal of Banking & Finance, 1999)
We employ a procedure suggested by the Department of Justice's Merger Guidelines (but never before applied to banking) to determine whether nonbank financial institutions should be included as participants in defining the product market relevant to antitrust analyses of proposed bank mergers. We estimate bank “residual supply” relationships indicating the responsiveness of small-scale deposit funds supplied by consumers to the level of interest rates offered for such deposits. Estimated elasticities of residual deposit supply are quite small, implying that only commercial banks should be included as participants in the “antitrust market” relevant to proposed bank mergers.